Family caregivers’ perception and response to COVID-19 in caring for older adults with chronic diseases: A qualitative study - Bahtiar Bahtiar; Nurlaila Fitriani; Dwi Nopriyanto; Ida Ayu Kade Sri Widiastuti; Arief Andriyanto; Ikbal Fradianto; Eriyono Budi Wijoyo (Lentera Perawat, 2026)
Background: The older adult is the vulnerable group to infecting COVID-19 and most of them live with their families. The family must take care of them while they face various problems during the pandemic. It will probably tend to more stress and burden so the understanding of their perception and response on dealing with older adults with chronic diseases is vital. Objective: This study explored exploring about perceptions and responses of family caregiver’s older adults with chronic diseases about COVID-19 disease. Methods: The study used qualitative descriptive phenomenology by using online semi-structured interviews with family caregivers of older adults with chronic diseases in Samarinda, Indonesia from September to November 2021. Sixteen family caregivers of older adults participated that was using purposive sampling method. The data analysis conducted by Collaizi technique and rigor process were included peer debriefing with peers, member checking of the outcome, and inquiry audit.  Results: After qualitative analysis, three main themes emerged: 1) Views of older adult families on covid-19 disease (positive and negative views on Covid-19 disease); 2) Older adult family caregiver responses in facing covid-19 vaccination of older adult with chronic diseases (negative thoughts about vaccinations, family efforts to facilitate vaccination for the older adult); 3) Families facilitate traditional medicine are an option that is of interest to the older adult to prevent and deal with covid-19 disease (opinions of the older adult to consume herbal medicine, reasons for older adult consuming herbal medicine). Conclusion: This study showed that Indonesian older adult family caregivers have various perceptions and responses to older adults with chronic diseases during the pandemic. The government needs to enhance health promotion regarding COVID-19 and vaccination. Older people commonly use herbal medicine, so information about ingredients and dose must be educated properly.